PENGEMBANGAN MEDIA CANVA BERBASIS ETNOMATEMATIKA PADA MATERI BANGUN RUANG MENGGUNAKAN MODEL RME UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V SDN 105331 PUNDEN REJO - Eka Syafitri, Desi; Ahmad Landong; Muhammad Noer Fadlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to improve understanding of mathematical concepts for class V students at SDN 105331 Punden Rejo. The research uses the (R&D) method with the ADDIE model to produce a product. The ADDIE model consists of 5 analysis stages, namely, design, development, implementation and evaluation. The research results from the implementation of ethnomathematics-based Canva media development have a validity percentage of 96% based on the assessment of material experts and 80% according to the assessment of media experts so that the development media is classified as very valid and its validity has been tested. The ethnomathematics-based Canva media that has been developed has a test score of 94.25% so that the development media is classified as very practical to apply in the learning process. The Canva media product based on Javanese cultural ethnomathematics which was developed using the RME model was considered effective in increasing students' understanding of mathematical concepts in class V at SDN 105331 Punden Rejo with a percentage of 85%.